Tinjauan Pelaksanaan Informed Concent Pemeriksaan Kontras Colon in Loop di Instalasi Radiologi RSUD Kota Yogyakarta - Zhazha Sulistya Nengrum; Eniyati Eniyati; Zakharias KP; Ika Fitria A (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2022)
Background: Medical records play a major role in improving the quality of medical services in hospitals. In the patient’s medical record section, there are several sheets, one of which is the Informed Consent sheet. Informed consent plays a major role for service providing medical facilities, because on the sheet it can create an agreement on health actions. Meanwhile, in the implementation of informed consent there are still discrepancies in its implementation. Purpose: To determine the implementation of informed consent for colon in loop contrast examination at the radiology installation of the Yogyakarta City Hospital. Method: This research was used the descriptive research methods using a qualitatif approach that is in depth interviews. Result: The results showed that the implementation of informed consent at the Yogyakarta City Hospital was not in accordance with the rules, namely in the implementation of informed consent there were still some that were carried out orally. Items in the delivery of informed consent include, at least include the patient’s diagnosis, the action to be given, the procedur for action, action, and actions and alternative actions. Overall, the completeness of the informed consent was not comprehensive and precise. Conclusion: The implementation of informed consent has not been carried out properly and there are still incomplete and correct sheets. It is recommended to the officer who is responsible for filing out the sheet.